An investigation on structural and optical properties of nanocolumnar ZnTe thin films grown by glancing angle technique - R Zarei; M H Ehsani; H Rezaghiolipour Dizaji (Materials Research Express, 2020)
In this paper, Zinc Telluride (ZnTe) thin films have been deposited on glass substrate by glancing angle deposition (GLAD) technique at different flux angles. The structural and optical properties of the prepared specimens have been studied with the help of x-ray diffraction (XRD), FESEM, and UV–vis analyses, respectively. According to these tests, remarkable changes in the morphology and the structure of the as-prepared samples have occurred. More significantly, using UV–vis analysis the optical properties including refractive index and band gap energy of the samples have been modified at higher deposition angles, which are promising to be applicable in optoelectronic devices.